Ambulatory and hospitalized patients with suspected and confirmed mpox: an observational cohort study from BrazilResearch in context - Mayara Secco Torres Silva; Carolina Coutinho; Thiago Silva Torres; Eduardo Peixoto; Ronaldo Ismério; Flavia Lessa; Estevão Portela Nunes; Brenda Hoagland; Amanda Dolores Echeverria Guevara; Matheus Oliveira Bastos; Isabel Cristina Ferreira Tavares; Maria Pia Diniz Ribeiro; et al. (Elsevier, 2023)
Summary: Background: By October 30, 2022, 76,871 cases of mpox were reported worldwide, with 20,614 cases in Latin America. This study reports characteristics of a case series of suspected and confirmed mpox cases at a referral infectious diseases center in Rio de Janeiro, Brazil. Methods: This was a single-center, prospective, observational cohort study that enrolled all patients with suspected mpox between June 12 and August 19, 2022. Mpox was confirmed by a PCR test. We compared characteristics of confirmed and non-confirmed cases, and among confirmed cases according to HIV status using distribution tests. Kernel estimation was used for exploratory spatial analysis. Findings: Of 342 individuals with suspected mpox, 208 (60.8%) were confirmed cases. Compared to non-confirmed cases, confirmed cases were more frequent among individuals aged 30-39 years, cisgender men (96.2% vs. 66.4%; p < 0.0001), reporting recent sexual intercourse (95.0% vs. 69.4%; p < 0.0001) and using PrEP (31.6% vs. 10.1%; p < 0.0001). HIV (53.2% vs. 20.2%; p < 0.0001), HCV (9.8% vs. 1.1%; p = 0.0046), syphilis (21.2% vs. 16.3%; p = 0.43) and other STIs (33.0% vs. 21.6%; p = 0.042) were more frequent among confirmed mpox cases. Confirmed cases presented more genital (77.3% vs. 39.8%; p < 0.0001) and anal lesions (33.1% vs. 11.5%; p < 0.0001), proctitis (37.1% vs. 13.3%; p < 0.0001) and systemic signs and symptoms (83.2% vs. 64.5%; p = 0.0003) than non-confirmed cases. Compared to confirmed mpox HIV-negative, HIV-positive individuals were older, had more HCV coinfection (15.2% vs. 3.7%; p = 0.011), anal lesions (45.7% vs. 20.5%; p < 0.001) and clinical features of proctitis (45.2% vs. 29.3%; p = 0.058). Interpretation: Mpox transmission in Rio de Janeiro, Brazil, rapidly evolved into a local epidemic, with sexual contact playing a crucial role in its dynamics and high rates of coinfections with other STI. Preventive measures must address stigma and social vulnerabilities. Funding: Instituto Nacional de Infectologia Evandro Chagas, Fundação Oswaldo Cruz (INI-Fiocruz).